Effects of Human Capital and Social Capital on Dropping Out of High School in the South - Mark H. Smith; Lionel J. Beaulieu; Glenn D. Israel (Journal of Research in Rural Education, 1991)
This paper assesses the effects of human capital and social capital on the probability of a person dropping out of high school, using the High School and Beyond data set. Utilizing logistic regressi n, predicted dropout rates are uncovered for students whose families and communities differ in human and social capital, controllmg for financial capital, race, ethnicity, and rural-urban residence. The effects of human and social capital variables combine to make substantial differences in predicted dropout rates.